Analisis Potensi Limbah Tinja Sebagai Bahan Bakar Alternatif : Analisis potensi limbah tinja sebagai bahan bakar alternatif - Aldi pratama (Institut Riset dan Publikasi Indonesia, 2025)
Human feces is an abundant organic waste that poses environmental risks if not managed properly. One sustainable solution is to convert it into renewable energy in the form of biogas. This study aims to analyze the potential of utilizing human feces as an alternative fuel source at the Jabal Nur Islamic Boarding School in Kandis, Riau, Indonesia. A quantitative approach was used, incorporating both primary and secondary data. The results indicate that with 820 students, the boarding school produces approximately 328 kg of feces per month, which can generate around 60.5 m³ of biogas. This biogas can reduce LPG consumption by 27.48 kg per month. The economic feasibility analysis reveals that while the project is environmentally viable, it is not yet financially profitable, with a Net Present Value (NPV) of -Rp1,174,700, a Net Benefit-Cost Ratio (Net B/C) of 0.856, and a Payback Period (PBP) of 7.18 years. Nevertheless, human feces-derived biogas holds significant potential as an environmentally friendly and sustainable alternative energy solution.